Variations in stroke incidence and survival in 3 areas of Europe - Kolominsky-Rabas, Peter; Wolfe, Charles D. A.; Giroud, Maurice; Dundas, Ruth; et al. (Stroke, 2000)
Background and Purpose - Comparison of incidence and case-fatality rates for stroke in different countries may increase our understanding of the etiology of the disease, its natural history, and management. Within the context of an aging population and the trend for governments to set targets to reduce stroke risk and death from stroke, prospective comparison of such data across countries may identify what drives the variation in risk and outcome. Methods - Population-based stroke registers, using multiple sources of notification, ascertained cases of first in a lifetime stroke between 1995 and 1997 for all age groups. The study populations were in Erlangen, Germany; Dijon, France; and London, UK. Crude incidence rates were age-standardized to the European population for comparative purposes. Case-fatality rates up to 1 year after the stroke were obtained, and logistic regression adjusting for age group, sex, and pathological subtype of stroke was used to compare survival in the 3 communities. Results - A total of 2074 strokes were registered over the 3 years. The age-standardized rate to the European population was 100.4 (95% CI 91.7 to 109.1) per 100 000 in Dijon, 123.9 (95% CI 115.6 to 132.2) in London, and 136.4 (95% CI 124.9 to 147.9) in Erlangen. Both crude and adjusted rates were lowest in Dijon, France. The incidence rate ratio, with Dijon as the baseline comparison (1), was 1.21 (95% CI 1.09 to 1.34) in London and 1.37 (95% CI 1.22 to 1.54) in Edangen (P<0.0001). There were significant differences in the proportion of the subtypes of stroke between populations, with London having lower rates of cerebral infarction and higher rates of subarachnoid hemorrhage and unclassified stroke (P<0.001). Case-fatality rates varied significantly between centers at 1 year, after adjustment for age, sex, and subtype of stroke (35% overall, 34% Erlangen, 41% London, and 27% Dijon; P<0.001). Conclusions - The impact of stroke is considerable, and the risk of stroke varies significantly between populations in Europe as does the risk of death. The striking differences in survival require clarification but lend weight to the evidence that stroke management may differ between northern and central Europe and influence outcome.
Created from Fastlane, Scopus look-up
Keywords: Epidemiology; Incidence; Mortality